In Silico Prediction of Binding Affinities of Hybrid Molecules of Benzothiazole Linked with Hydroxamic Acid by Disulfide Bond and Certain Linkers with HDAC8 Enzyme - Mayssam Hazem; Shakir M. Alwan (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2024)
A new hybrid molecule of Benzothiazole cross-linked with hydroxamic acid through an amino acid or aminoalkanoic acid were synthesised. All the synthesized hybrid molecules (1-5) were subjected to molecular docking studies to evaluate their binding affinities with histone deacetylase enzyme (HDAC8, PDB ID: 1T69) and recorded lower ΔG (-8.276, -10.093, -8.647, -6.315, -8.676 kcal/mole, respectively) than the reference ligand (Vorinostat, suberoylanilide hydroxamic acid, SAHA -5.375 kcal/mole).